Dispositivi e critica letteraria (ENTHYMEMA, 2010)
The article deals with the concept of «dispositif» (device) through the analysis of the connection with its antecedents in Foucault’s thought: «formation discursive» (discursive formation) and «positivité» (positivity). If one defines the device as a whole destined to deteriorate and to surpass itself, the theory of these breaking points becomes clear through the observations about the historical times of Koselleck and Ricœur. The initiative (or «strength of the present») that allows a system to transform itself is identified, within literary criticism, in an articulate role of the author, conjunction and conflict point of an ontology of intentions and an ontology of events. Using these concepts we can read again one of the most important critical essays of the XXth century: Mimesis by Erich Auerbach.